Why fathers cry at night : a memoir in love poems, letters, recipes, and remembrances - Alexander, Kwame (Little, Brown & Company, Hachette Book Group, 2023)
Kwame Alexander shares snapshots of a man learning how to love. He takes us through stories of his parents: from being awkward newlyweds in the sticky Chicago summer of 1967, to the sometimes-confusing ways they showed their love to each other, and for him. Alexander attempts to deal with the unraveling of his marriage and the grief of his mother's recent passing while sharing the solace he found in learning how to perfect her famous fried chicken dish. With an open heart, Alexander weaves together memories to understand his greatest love for his daughters.